Epidemic Diseases and Chinese Medicine: Example of Severe Acute Respiratory Syndrome and COVID-19 - Jean-Claude Dubois (Chinese Medicine and Culture)
Epidemic diseases, known and studied in China since antiquity, are one of the main chapters of the School of Exogenous Febrile Diseases (温病学派). Along with the legends about epidemic demons, China has developed over the centuries a medical approach based on the teachings of Huang Di Nei Jing (《黄帝内经》Internal Classic), Nan Jing (《难经》Classic of Difficulties), and Shang Han Lun (《伤寒论》Treatise of Harmful Cold). However, it was in the 17th century, after the great break of the Song, Jin, and Yuan eras that an innovative spirit Wu Youxing (吴有性) first foresaw the existence of microorganisms as we know them now. His Wen Yi Lun (《瘟疫论》Treatise on Pestilences) foreshadows an original approach to epidemic diseases, particularly emerging infectious diseases of the 21st century: severe acute respiratory syndrome 2003–2004 and the COVID-19 pandemic are perfect examples. In this first article, which will be followed by two others, we will examine the classical and modern Chinese definitions of these dreadful plagues.